International Small and Medium-Sized Enterprises Internationalization Patterns, Mode Changes, Configurations and Success Factors - Olejnik, Edith; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
With growing international business, small and medium-sized enterprises (SMEs) have been faced with increased competition, but also with enhanced opportunities. Edith Olejnik addresses four major issues within the context of SMEs$1 (Binternationalization process: First, she identifies the three different internationalization patterns that SMEs take and analyzes how these patterns develop over time. Second, she looks at dynamic changes of foreign operation modes and the managerial reasons for these changes. Third, she derives an empirical classification of smaller family firms and profiles them using a comprehensive set of organizational variables. Fourth, she investigates the relationship between firm-level processes and dynamic capabilities in driving the international performance of SMEs. Based on theoretical considerations and empirical analyses this work provides important implications for research and management practice. Contents Internationalization Patterns and Strategies Foreign Operation Modes Changes Organizational Configurations of International Family Firms Firm-level Success Factors Target Groups Researchers and students focusing on international business, entrepreneurship and management Executives and managers interested in the internationalization and successful global management of SMEs The Author Dr. Edith Olejnik received her doctoral degree from the University of Trier, where she worked at the chair for Marketing and Retailing.s
Internationalization Patterns and Strategies -- Foreign Operation Modes Changes -- Organizational Configurations of International Family Firms -- Firm-level Success Factors.
Keywords: Economics; Entrepreneurship; Economics/Management Science; Entrepreneurship; Business Strategy/Leadership.